Wave modelling – The state of the art - Cavaleri, L.; Alves, J.-H.G.M.; Ardhuin, F.; Babanin, A.; Banner, M.; Belibassakis, K.; Benoit, M.; Donelan, M.; Groeneweg, J.; Herbers, T.H.C.; Hwang, P.; Janssen, P.A.E.M.; et al. (Progress in oceanography, 2007)
This paper is the product of the wave modelling community and it tries to make a picture of the present situation in this branch of science, exploring the previous and the most recent results and looking ahead towards the solution of the problems we presently face. Both theory and applications are considered. The many faces of the subject imply separate discussions. This is reflected into the single sections, seven of them, each dealing with a specific topic, the whole providing a broad and solid overview of the present state of the art. After an introduction framing the problem and the approach we followed, we deal in sequence with the following subjects: (Section) 2, generation by wind; 3, nonlinear interactions in deep water; 4, white-capping dissipation; 5, nonlinear interactions in shallow water; 6, dissipation at the sea bottom; 7, wave propagation; 8, numerics. The two final sections, 9 and 10, summarize the present situation from a general point of view and try to look at the future developments.